Inside Cover: Enantiomeric Excess Sensitivity to Below One Percent by Using Femtosecond Photoelectron Circular Dichroism (ChemPhysChem 8/2016). Issue 8 (5th April 2016) - Kastner, Alexander; Lux, Christian; Ring, Tom; Züllighoven, Stefanie; Sarpe, Cristian; Senftleben, Arne; Baumert, Thomas
Abstract : Laser‐based approaches for chiral recognition of randomly oriented molecules in the gas phase offer sub one percent sensitivity to enantiomeric excess in nearly racemic as well as nearly enantiopure samples. More information can be found in the Full Paper by T. Baumert et al. onpage 1119 in Issue 8, 2016 (DOI:10.1002/cphc.201501067 ).